The First Tourist Cruise in the Soviet Arctic - Barr, William (ARCTIC, 1980)
In the summer of 1931 the icebreaking steamer Malygin sailed from Arkhangel'sk, bound for Zemlya Frantsa Iosifa with the first Soviet tourist cruise to the Arctic, the main objective being to visit the various historic sites of the archipelago. The steamer also made a rendezvous with the airship Graf Zeppelin at Bukhta Tikhaya. Other historic sites visited included Mys Flora, Bukhta Teplitsa and Camp Zeigler on Ostrov Al'dzher. Of special historical interest was the recovery of a message left by Baldwin at his satellite camp at the west end of Ostrov Al'dzher. A significant contribution to the charting of the archipelago was the discovery that Jackson's "Arthur Island" and "Alfred Harmsworth Island" were in fact a single island, for which the name Ostrov Artura was retained. Surprises such as this, a brief accidental grounding, and a three-day drift amongst ice and in dense fog probably combined to persuade the Soviet authorities not to repeat this experiment for several decades.